Low-Cost Albedo Sensing and Thermographic Analysis for Urban Heat Island Monitoring - Sausen, Jordan P.; Alves, Michael D. C.; Polette, Marcus; Campos, Mauricio de; Vieira, Gustavo S.; Andrade, Samuel C. P. T. de (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA); 2026: Anais do XVII Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos NaturaisDO - 10.5753/wcama.2026.22290, 2026)
Urban heat island effects are strongly influenced by surface radiative properties and urban morphology. This study presents the development and experimental evaluation of a low-cost embedded sensing platform for estimating surface albedo as part of an urban environmental monitoring framework. A field campaign was conducted in Itajaí, Brazil, where infrared thermography was used to characterize thermal contrasts across representative urban locations under sun and shade exposure conditions. In parallel, the proposed sensing platform was used to estimate surface albedo using a low-cost embedded architecture. The results provide an initial characterization of urban termal behavior across representative urban environments. This work represents a preliminary step toward the deployment of IoT-based environmental sensors integrated into a future LoRaWAN infrastructure.